The Impaired Sustained Attention in Children with ADHD: Relevant Factors and Clinical Implications - Liang, Zhiling (Transactions on Materials, Biotechnology and Life Sciences, 2024)
Attention-deficit/hyperactivity disorder (ADHD) is a neurodevelopmental condition that profoundly disrupts a child’s capacity to maintain focus, impacting various aspects of their daily existence. This article delves into the intricate realm of compromised sustained attention in children diagnosed with ADHD, offering an exhaustive examination of the contributing factors and their clinical implications. Employing extensive research, this research delves into the multifaceted facets of attention deficits associated with ADHD, encompassing distinct attentional components, susceptibility to distractions, attention patterns, processing speed, autonomic regulation, and developmental considerations. By unraveling these discoveries, the exploration acquires valuable insights into the hurdles confronted by children grappling with ADHD when it comes to sustaining attention. Furthermore, emphasizing the significance of tailored interventions aimed at addressing specific attention-related elements. By shedding light on the complexity of impaired sustained attention in ADHD, this article advances researchers’ comprehension of this condition and lays the groundwork for more efficacious diagnostic and therapeutic approaches. This review can help improve the lives of children affected by ADHD by fostering a more nuanced understanding of the challenges they face in their daily lives.